Heat capacity and thermodynamic functions of crystalline and amorphous forms of Lovastatin - Maria Brycka; Agata Olszewska; Natalie Parkinson; Christopher Hoban; Anna Czerniecka-Kubicka; Marek Pyda; Brian F. Woodfield; Marcin Skotnicki (Scientific Reports)
Abstract The thermal behavior of crystalline and amorphous lovastatin was studied using advanced thermal analysis, including the Quantum Design Physical Property Measurement System and Differential Scanning Calorimetry. Equilibrium lines for liquid and solid states were determined from experimental heat capacity values, allowing for the calculation of state functions. The Kauzmann temperature (T K) was estimated based on enthalpy and entropy as a function of temperature. Physical ageing studies were conducted at 10 °C for various durations, from 15 min up to 72 h and fictive temperatures were determined for the aged samples. Quantitative thermal analysis provided essential thermodynamic data for both the crystalline and amorphous phases of lovastatin.